Analyzing the Impact of Inward FDI and Economic Growth on CO2 Emissions of Ukraine - Kayani, Farrukh Nawaz; Sadiq, Misbah (International Journal of Energy Economics and Policy, 2022)
The study investigated the impact of foreign direct investment and economic growth, upon carbon emissions of Ukraine. The annual data for the study has been extracted from the World Bank Development Indicators for the period 1990 to 2019. The study variables are foreign direct investment, economic growth, and carbon emissions. We started our analysis based on the autoregressive distributed lag (ARDL) model as being use quite extensively in the existing literature. However, we faced the issue of multicollinearity, then we applied the Ordinary Least Square technique and system generalized method of moments as alternative estimation techniques. The main analysis is based on the Ordinary Least Square technique, whereas robustness has been carried out under the system’s generalized method of moments. Both estimation techniques confirmed the significant and positive relationship between our study’s variables. The results indicate that in Ukraine the inflows of foreign direct investment and economic growth have led to higher carbon emissions.